LUMINESCENCE DATING OF LOESS-PALAEOSOL SEQUENCES AND COVERSANDS: METHODOLOGICAL ASPECTS AND PALAEOCLIMATIC IMPLICATIONS - Singhvi A.K.; Rao M.Someshwar; Bateman M.D.; Bluszcz A. (My University, 2001)
Of the terrestrial archives, loess–palaeosol sequences provide a most complete record of climatic change. This may be compared with the Marine oxygen isotope stratigraphy, and may help in the reconstruction of past atmospheric circulation patterns. Numerical chronometry of loess–palaeosol sequences has generally been based on correlation of variations in climatic proxies (such as magnetic susceptibility and particle sizes) with Marine isotopic data. Such chronometric assignments involve implicit assumptions about the constancy of sedimentation rates and particle fluxes through time. This review presents a brief survey of the present status, methodology, outstanding problems and interpretational aspects of luminescence techniques, and discusses the import of luminescence ages on global land–sea correlations. Statistical analysis of the ages suggests episodicity of loess accumulation with extended periods of quiescence. Recent luminescence dating studies on closely spaced samples also lead to a similar inference. Luminescence ages imply high variability in loess sedimentation rates. This conflicts with the assumption, made in some current attempts to correlate loess records with marine records, of almost constant particle fluxes. A review of source-proximal coversand deposits of northwest Europe is also presented. Evidence of the onset of coversand deposition at 15 ka, with a peak in accretion during the Younger Dryas and subsequent minor reactivation episodes, is discussed.